Alih Kode (Code-Switching) Pada Status Jejaring Sosial Facebook Mahasiswa - Lusi Lian Piantari (JURNAL Al-AZHAR INDONESIA SERI HUMANIORA, 2011)
Code-switching, a code change in language use, is a language phenomenon in bilingual or multilingual societies.The rapid development of technology causes many language changes also occur in internet including social networking sites such as Facebook. This research is about how the code-switching from Bahasa Indonesia to English is demonstrated in Facebook status of UAI students. The research focuses on the types of code-switching, language patterns, themes, and function of code-switching. Data are code-switched Facebook status analyzed with theories of code-switching by Poplack (1980), Gumperz (1982), and Romaine (2000). This research is a descriptive qualitative research. The result demonstrates the types of code-switchings in Facebook status are inter-sentential and intra-sentential switchings. Both types of code-switchings are expressed in words, phrases, and sentences. Code-switched words are nouns, adjectives, adverbs, and verbs. Phrases in code-switching are noun, adjective, adverbial, and prepositional phrases. Whereas code-switched sentences found in the Facebook status are single, compound, and complex sentences. The themes in code-switched Facebook status cover the themes related with social, academic, and personal lives of the language users.  The functions of code-switching in the analyzed status are to express emotion and particular meanings, to impose specific meanings, and to show language user’s identities.